PROMOTING DECENT LIVING FOR DAILY WORKERS IN ACCORDANCE WITH INDONESIAN GOVERNMENT REGULATION NO. 36 OF 2021 ON WAGES - Thamrin S; Surizki Febrianto; Lidia febrianti; Puti Mayang Seruni (Universitas Syiah Kuala, 2023)
Daily workers often express concerns about whether their wages are sufficient to provide them with a decent standard of living. Government Regulation Number 36 of 2021 regarding Wages states that the calculation of minimum wage is determined based on economic and employment conditions, which differs from the previous regulation that emphasized setting the minimum wage according to a decent living standard. This change has had a significant impact on wage determination. This study aims to examine how the latest wage policy can contribute to ensuring a decent living for daily laborers in Indonesia. The study adopts a normative legal research method and provides analytical descriptive data. It involves analyzing legal materials and comparing them with the main issues at hand. The calculation of wages for daily laborers is based on factors such as working hours, working days, or work results. However, it is important to note that the mandatory wage component for daily workers is solely the minimum wage, excluding allowances and non-wage income components. This confirms that the current wage structure for daily workers falls short of meeting the needs of a decent life for both workers and their families, as it solely relies on working hours. Therefore, it is crucial to prioritize efforts to improve the standard of living for daily workers in Indonesia.